2017
DOI: 10.3233/jad-170177
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine Attenuates Oxidative Stress and Neuroinflammation Induced by Amyloid-β Through Modulation of Glutathione Metabolism

Abstract: Oxidative stress and neuroinflammation are mainly involved in the pathogenic mechanisms of Alzheimer's disease (AD). Amyloid-β (Aβ), the main component of senile plaques, is a kind of strong inducer of oxidative stress. Glutathione is an endogenous antioxidant protecting cells from oxidative injury. S-adenosylmethionine (SAM) produced in the methionine cycle is the primary methyl donor and the precursor of glutathione. In this study, the Aβ intrahippocampal injection rat model and cultured SH-SY5Y cells were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…This could be an adaptive process used by the delayed birds to attenuate their stress response as this is reported for the domesticated birds compared to their wild counterparts [43]. Furthermore, the contribution of 3 metabolites known for their antioxidant effects [44, 45], i.e. citrulline (LC, − 1.40), taurine (LC, − 0.76), and adenosylmethionine (LC, − 0.12) was higher in the delayed groups, also suggesting an adaptive response of the D chickens to negative postnatal events.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an adaptive process used by the delayed birds to attenuate their stress response as this is reported for the domesticated birds compared to their wild counterparts [43]. Furthermore, the contribution of 3 metabolites known for their antioxidant effects [44, 45], i.e. citrulline (LC, − 1.40), taurine (LC, − 0.76), and adenosylmethionine (LC, − 0.12) was higher in the delayed groups, also suggesting an adaptive response of the D chickens to negative postnatal events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that in valproic acid (VPA)-exposed dams, treatment with high doses of folic acid, vitamin E and the methyl donor methionine could ameliorate or prevent most of the VPA-induced damage [100,101]. S-adenosylmethionine (SAM) is known to reduce oxidative stress in several organs [102][103][104]. In the brain, this molecule inhibited lipid peroxidation and supported the glutathione system [102].…”
Section: Targeting Ros To Treat Asdmentioning
confidence: 99%
“…Many studies show that SAM administration alleviates oxidant stress and restores the tissues. For example, Li et al [ 23 ] found that SAM administration protects cells and inhibits oxidative stress induced by amyloid- β , and it activates endogenous antioxidant system by restoring the normal GSH/GSSG ratio and increasing the activities of glutathione peroxidase (GSH-Px), glutathione-S-transferase (GST), and superoxide dismutase (SOD).…”
Section: Methioninementioning
confidence: 99%